ETHICS AND POLICY CHALLENGES IN THE DIGITIZATION OF CULTURAL HERITAGE - Kanthe, Rajesh Uttam; Soorya, Amutha M.V.; Patel, Snehal; Wankhade, Nisha; Barruga, Milagros B; Jadhav, Swati Sachin (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The process of cultural heritage digitization has turned to be one of the most important strategies of preservation of the historical artifacts, manuscripts, art pieces, and the digital age intangible traditions. Cultural institutions can preserve heritage resources, capture more, and make them more accessible and then ever before through the use of high-tech technologies such as the features of 3D scanning, artificial intelligence, digital archiving, and cloud data storage. The digitization also increases accessibility among researchers, educators, and the general population as well as preserving the cultural materials which are easily prone to damage, natural calamities and war. Nevertheless, the fast pace of digital heritage projects pose the major ethical and policy issues. The problems of the intellectual property rights, cultural artifacts ownership, and presentation of culturally sensitive materials have to be considered. In addition, the problem of community approval and the rights of indigenous people also raises the question of the inclusivity and cultural sensitivity of digitalization activities. International and national policy and legal frameworks are also very important in regulating the preservation of digital heritage especially in areas like copyright, licensing and cross-border data sharing.